Clinical efficacy of topical Avena sativa versus Betamethasone in chronic pruritus due to sulfur mustard exposure - M Shohrati; M Davoudi; Sh Rezazadeh; B Najafian (Institue of Medicinal Plants, ACECR, 2017)
Background: Avena sativa, a well-known herbal medicine; has been used in various skin diseases such as eczema, burn and pruritus. Objective: The objective of this study was to evaluate the effect of this herbal medicine for treatment of chronic pruritus in Sulfur Mustard (SM) exposed patients. Methods: Veterans who referred to Baghiat-Allah dermatologic clinic for itching problems were examined by a dermatologist and randomly assigned in three different groups. Group A received ointment derived from Avena sativa plant, group B, placebo and group C, betamethasone 0.1% cream twice a day for 4 weeks. Twenty five patients were included in each group. A visual analogue scale were used for assessment of severity of pruritus and 2 questionnaire for quality of life and quality of sleep were filled for each patient.   Results: Pruritus severity after the study by VAS method was significantly decreased in all the groups, but betamethasone group showed the largest decrease (-2.4, P<0.001). The average quality of life based on DLQI criteria and quality of sleep based on PSQI after the treatment showed the most significant difference in betamethasone group (3.52, P<0.001 and  0.96, P=0.001 respectively). Although Avena sativa showed significant effect on these criteria but it was only superior to placebo and not as effective as betamethasone.   Conclusion: The result demonstrated that Avena sativa ointment reduced chronic pruritus, increased quality of life and quality of sleep in patients exposed to SM but betamethasone was superior in all aspects.